Chapter Parte seconda. Buone pratiche di Public History per la formazione e il territorio (Public History of Education. Teorie, esperienze, strumenti, 2022)
In keeping with the ten essays collected in the first part of the volume, this section proposes thirty Best Practices files, selected from the most recent and stimulating ones. These are real models of educational action thanks to which we can offer a first look of some of the many projects based on the relationship between school, university and territory. Models, therefore, in which Public History practices have found, or can find, fertile ground.